Improving Organizational Effectiveness in Manufacturing: A study of selected manufacturing plant in Durban, South Africa - Sokhetye, Anathi (Acta Carolus Robertus, 2022)
Improving organizational effectiveness in Manufacturing plants has become important constantly going back to the drawing board to observe how to measure effectiveness to manufacturing to achieve results based on organizational goals, is it therefore important to be aware of challenges in organizational effectiveness  which employees may face because employees are the heart of the manufacturing plant a product goes from being a raw material to a finished good because of employees, The various departments can always review these measures to help the manufacturing company achieve the organizational objectives it has set out to achieve results that will result in organizational effectiveness. The study is relevant for the selected industry sector as there have some studies. which indicate that some manufacturing plants may not be operating at their, optimum on account of the lack of organizational effectiveness, this study will speak to those needs. Findings from the study will be relevant currently as lessons learnt can be applied immediately
Keywords: effectiveness; manufactouring; improvement